2018
DOI: 10.1016/j.dsr2.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Composition of abyssal macrofauna along the Vema Fracture Zone and the hadal Puerto Rico Trench, northern tropical Atlantic

Abstract: We analyzed composition and variations in benthic macrofaunal communities along a transect of the entire length of the Vema-Fracture Zone on board of RV Sonne (SO-237) between December 2014 and January 2015 in order to test whether the Mid-Atlantic Ridge serves as a barrier limiting benthic taxon distribution in the abyssal basins on both sides of the ridge or whether the fracture zone permits the migration of species between the western and eastern abyssal Atlantic basins. The Puerto Rico Trench, much deeper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Additionally, Hemichordata and Ctenophora were also firstly reported in the Yap Trench. Hemichordata is a prominent member of the epibenthic community in the deep sea (Osborn et al, 2011), which has been reported from several hadal trenches in both the Pacific and Atlantic Ocean (Jamieson, 2015;Brandt et al, 2018). Besides the single observation of Hemichordata, many of their traces were observed majorly from the surface of sediment, just as previous observations (Heezen and Hollister, 1971;Lemche et al, 1976;Gallo et al, 2015).…”
Section: Hadal Fauna In the Yap Trenchsupporting
confidence: 67%
See 2 more Smart Citations
“…Additionally, Hemichordata and Ctenophora were also firstly reported in the Yap Trench. Hemichordata is a prominent member of the epibenthic community in the deep sea (Osborn et al, 2011), which has been reported from several hadal trenches in both the Pacific and Atlantic Ocean (Jamieson, 2015;Brandt et al, 2018). Besides the single observation of Hemichordata, many of their traces were observed majorly from the surface of sediment, just as previous observations (Heezen and Hollister, 1971;Lemche et al, 1976;Gallo et al, 2015).…”
Section: Hadal Fauna In the Yap Trenchsupporting
confidence: 67%
“…Our observations showed that benthic sessile fauna, such as sponges and actiniarians, were mostly restricted to hard or mixed substrates, whereas small crustaceans such as mysids, amphipods, and munnopsids dominated the sedimentary seafloor ( Figure 7B). A trend of reduction in the munnopsid abundance from abyssal to hadal depths was revealed in the Puerto-Rico Trench and Kuril-Kamchatka Trench (Brandt et al, 2018;Malyutina and Brandt, 2020). In contrast, the abundance of munnopsids increased with depth in the Yap Trench, which may be attributed to the higher sediment coverage in the hadal zone.…”
Section: Habitat Heterogeneitymentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, more material was collected on board RV Meteor in 2011 during the Icelandic Animals Genetic and Ecology (IceAGE) program in waters of Iceland 22 , and on board RV Sonne , in 2014/2015 on both sides of the Mid-Atlantic Ridge at the Vema Fracture Zone during the Vema-TRANSIT project 23 , and in 2015 from the Central Pacific within the framework of the Joint Programming Initiative Healthy and Productive Seas and Oceans platform (JPI Oceans) 24 . That material was collected, fixed and handled following protocols for fixation as described in Riehl et al .…”
Section: Methodsmentioning
confidence: 99%
“…Deep-sea benthos fosters a high diversity of invertebrates with peracarid crustaceans like Isopoda being particularly species-rich (Wilson & Ahyong, 2015;Brandt et al, 2018). The underlying factors that shaped this diversity and the potential role of past climatic changes or physical barriers, such as deep-sea ridges, are not well understood.…”
Section: Introductionmentioning
confidence: 99%